Shear Resistance Enhancement of Oil-Contaminated Railtrack Ballast with Rubber Circular Patch Formulation - Siti Farhanah, SM Johan; Chan, Chee Ming (Trans Tech Publications, Switzerland, 2016)
Railtrack ballast is a component in the track’s substructure. It plays the important role of transmitting and distributing the wheel load to the deeper track section, i.e. subgrade. The cause of ballast breakage is often due to repeated impact by the passing trains. Mostly the breakage occurs at the sharp corners of ballast. Oil contamination can also contribute to track deterioration. In this manner, caused by fuel leaking from the rolling stock and maintenance works of trains. Therefore, it results in shear strength reduction of the ballast layer as the ballast loose frictional resistance due to the oil contamination. In this study, the test results indicated that contact between rubber and ballast when the circular patches exposed to the oil-contaminated gravels (lubricant oil) could improve the shear resistance and have a better deformation. It was observed that the deformation of the oilcontaminated with circular patches was reduced compared to the ballast without circular patches. The improvement of shear resistance is due to the increased ductility of composite and breakage control. It is with nothing that the present study were conducted is static in a scaled down model. Therefore, it is necessary for the future research to be conducted with full-scale test under dynamic loading to mimics the actual rail traffic.